Welfare Effects of Agricultural Foreign Direct Investment in Developing Countries - Djokoto, Justice Gameli; Agyei Henaku, Kofi A. A-O; Badu-Prah, Charlotte (Frontiers in Sustainable Food Systems, 2022)
Many developing countries have embraced policies to attract foreign direct investment into their respective economies including the agricultural sector to enhance technology transfer, employment, and trade among other benefits. On the other hand, foreign direct investment into the agricultural sector has been associated with competition with local agricultural produce from imported raw and processed products and land grabbing that has deprived farmers of land for cultivation. These could have implications for the investment and employment of indigenes in the agricultural sector and consequently welfare. This raises the question, does agricultural foreign direct investment promote or discourage welfare? In this paper, we assessed the welfare effects of agricultural foreign direct investment in developing countries. Using an unbalanced panel data of 51 developing countries from 1990 to 2019 with a fixed-effects estimator, we found that agricultural foreign direct investment promotes welfare in developing countries. Openness to trade, population growth, human capital, and infrastructure enhanced welfare. Whilst government expenditure did not promote welfare, inflation did not affect welfare. Whilst promoting foreign direct investment into agriculture, governments in developing countries must improve human capital, develop infrastructure, and pursue trade openness policies. Final government expenditure on goods and services needs to be redirected into funding projects and programmes that improve the health, education, and income of citizens, especially the poor.